Retraction note: Saraiva, R., & Arévalo, J. (2021). The reality of hospital libraries in central Portugal - Equipo Editorial (Biblios, 2022)
The authors of "The reality of hospital libraries in central Portugal", published in issue 81, pp 1-15; informed their willingness to retract the article. The reason is to publish the article in another journal. The Biblios Editorial Team accepts and proceeds to the retraction of the work, following the protocols of the Committee on Publication Ethics (COPE), and timely notified the authors.